Electrophysiologic alterations in patients with optic nerve hypoplasia - Janáky, M; Deák, A; Pelle, Z; Benedek, G (Documenta ophthalmologica, 1994)
The clinical and electrophysiologic data (electroretinograms and visual evoked potentials) were studied in 45 patients with optic nerve hypoplasia. The patients were divided into three fairly distinct groups on the basis of their electrophysiologic alterations. Group 1 consisted of 13 patients with almost extinguished visual evoked potentials and with mild electroretinographic alterations. These were the cases that are traditionally recognized as optic nerve hypoplasia. The serious visual impairment in these cases was accompanied by various developmental ophthalmologic and nonophthalmologic abnormalities. Group 2 included 26 patients without any significant visual evoked potential or electroretinographic alterations, but with overt funduscopic signs of optic nerve hypoplasia. These patients were consistently suffering from strabismus and/or amblyopia. The visual functions based on visual evoked potential and electroretinographic recordings could be fairly normal apart from a pathologic ophthalmoscopic picture characteristic of optic nerve hypoplasia. Group 3 included six patients with abnormal albeit well-recordable visual evoked potentials and subnormal or negative-type electroretinograms that suggested an accompanying retinal disease. This finding seems to prove that a subset of patients with optic nerve hypoplasia with nystagmus may have a primary retinal abnormality. Our study provides further evidence that optic nerve hypoplasia is not a uniform disease entity.